Hadith #67 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Once the Prophet (ﷺ) was riding his camel and a man was holding its rein. The Prophet (ﷺ) asked, “What is the day today?” We kept quiet, thinking that he might give that day another name. He said, “Isn’t it the day of Nahr (slaughtering of the animals of sacrifice)” We replied, “Yes.” He further asked, “Which month is this?” We again kept quiet, thinking that he might give it another name. Then he said, “Isn’t it the month of Dhul-Hijja?” We replied, “Yes.” He sai
Grade: Sahih

Hadith #299 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
(on the authority of his father) `Aisha said: “Whenever Allah’s Messenger (ﷺ) wanted to fondle anyone of us during her periods (menses), he used to order her to put on an Izar and start fondling her.” `Aisha added, “None of you could control his sexual desires as the Prophet (ﷺ) could.”
Grade: Sahih

Hadith #595 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Abu Sa`id Al-Khudri told my father, “I see you liking sheep and the wilderness. So whenever you are with your sheep or in the wilderness and you want to pronounce Adhan for the prayer raise your voice in doing so, for whoever hears the Adhan, whether a human being, a jinn or any other creature, will be a witness for you on the Day of Resurrection.” Abu Sa`id added, “I heard it (this narration) from Allah’s Messenger (ﷺ).”
Grade: Sahih

Hadith #1615 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
`Abdullah;- performed the Hajj and we reached Al-Muzdalifa at or about the time of the `Isha’ prayer. He ordered a man to pronounce the Adhan and Iqama and then he offered the Maghrib prayer and offered two rak`at after it. Then he asked for his supper and took it, and then, I think, he ordered a man to pronounce the Adhan and Iqama (for the `Isha’ prayer). (`Amr, a sub-narrator said: The intervening statement ‘I think’, was said by the sub-narrator Zuhair) (i.e. not by `Abdur-Rahman). T
Grade: Sahih

Hadith #1623 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I went out with `Abdullah , to Mecca and when we proceeded to am’ he offered the two prayers (the Maghrib and the `Isha’) together, making the Adhan and Iqama separately for each prayer. He took his supper in between the two prayers. He offered the Fajr prayer as soon as the day dawned. Some people said, “The day had dawned (at the time of the prayer),” and others said, “The day had not dawned.” `Abdullah then said, “Allah’s Messenger (ﷺ) said, ‘These two prayers have been sh
Grade: Sahih

Hadith #1685 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
`Abdullah, did the Rami from the middle of the valley. So, I said, “O, Abu `Abdur-Rahman! Some people do the Rami (of the Jamra) from above it (i.e. from the top of the valley).” He said, “By Him except whom none has the right to be worshipped, this is the place from where the one on whom Surat-al-Baqara was revealed (i.e. Allah’s Messenger (ﷺ)) did the Rami.”
Grade: Sahih

Hadith #1686 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
When `Abdullah, reached the big Jamra (i.e. Jamrat-ul-Aqaba) he kept the Ka`ba on the left side and Mina on his right side and threw seven pebbles (at the Jamra) and said, “The one on whom Surat-al- Baqara was revealed (i.e. the Prophet) had done the Rami similarly.”
Grade: Sahih

Hadith #1687 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I performed Hajj with Ibn Mas`ud , and saw him doing Rami of the big Jamra (Jamrat-ul-Aqaba) with seven small pebbles, keeping the Ka`ba on his left side and Mina on his right. He then said, “This is the place where the one on whom Surat-al-Baqara was revealed (i.e. Allah’s Messenger (ﷺ) ) stood.”
Grade: Sahih

Hadith #1692 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I heard my father who was the best man of his age, saying, “I heard `Aisha saying, ‘I perfumed Allah’s Apostle with my own hands before finishing his Ihram while yet he has not performed Tawaf-al- Ifada.’ She spread her hands (while saying so.)”
Grade: Sahih

Hadith #1746 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Ka`b bin ‘Ujra said that Allah’s Messenger (ﷺ) said to him (Ka`b), “Perhaps your lice have troubled you?” Ka`b replied, “Yes! O Allah’s Messenger (ﷺ).” Allah’s Messenger (ﷺ) said, “Have your head shaved and then either fast three days or feed six poor persons or slaughter one sheep as a sacrifice.”
Grade: Sahih

Hadith #1749 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
(Reporting the speech of Ka`b bin Umra) Allah’s Messenger (ﷺ) saw him (i.e. Ka`b) while the lice were falling on his face. He asked (him), “Have your lice troubled you?” He replied in the affirmative. So, he ordered him to get his head shaved while he was at Al-Hudaibiya. At that time they were not permitted to finish their Ihram, and were still hoping to enter Mecca. So, Allah revealed the verses of Al-Fidya. Allah’s Messenger (ﷺ) ordered him to feed six poor persons with one Faraq
Grade: Sahih

Hadith #2102 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
that his father said, “The Prophet (ﷺ) forbade the selling of gold for gold and silver for silver except if they are equivalent in weight, and allowed us to sell gold for silver and vice versa as we wished.”
Grade: Sahih

Hadith #2135 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
We were with the Prophet (ﷺ) when a tall pagan with long matted unkempt hair came driving his sheep. The Prophet (ﷺ) asked him, “Are those sheep for sale or for gifts?” The pagan replied, “They are for sale.” The Prophet (ﷺ) bought one sheep from him.
Grade: Sahih

Hadith #2215 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I got an agreement written between me and Umaiya bin Khalaf that Umaiya would look after my property (or family) in Mecca and I would look after his in Medina. When I mentioned the word ‘Ar64 Rahman’ in the documents, Umaiya said, “I do not know ‘Ar-Rahman.’ Write down to me your name, (with which you called yourself) in the Pre-Islamic Period of Ignorance.” So, I wrote my name ‘ `Abdu `Amr’. On the day (of the battle) of Badr, when all the people went to sleep, I went up the hil
Grade: Sahih

Hadith #2333 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Abu Hurairah (ra) said, “Allah’s Messenger (ﷺ) mentioned an Israeli man.” Abu Hurairah then told the whole narration). (At the end of the narration it was mentioned that the creditor) went out to the sea, hoping that a boat might have brought his money. Suddenly he saw a piece of wood and he took it to his house to use as firewood. When he sawed it, he found his money and a letter in it.
Grade: Sahih

Hadith #2513 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
We were one-hundred and thirty persons accompanying the Prophet (ﷺ) who asked us whether anyone of us had food. There was a man who had about a Sa of wheat which was mixed with water then. A very tall pagan came driving sheep. The Prophet (ﷺ) asked him, “Will you sell us (a sheep) or give it as a present?” He said, “I will sell you (a sheep).” The Prophet (ﷺ) bought a sheep and it was slaughtered. The Prophet ordered that its liver and other Abdominal organs be roasted. By Allah, t
Grade: Sahih

Hadith #2863 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
The Prophet (ﷺ) ordered me to let `Aisha sit behind me (on the animal) and to let her perform `Umra from at-Tan`im.
Grade: Sahih

Hadith #3012 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
While I was standing in the row on the day (of the battle) of Badr, I looked to my right and my left and saw two young Ansari boys, and I wished I had been stronger than they. One of them called my attention saying, “O Uncle! Do you know Abu Jahl?” I said, “Yes, What do you want from him, O my nephew?” He said, “I have been informed that he abuses Allah’s Messenger (ﷺ). By Him in Whose Hands my life is, if I should see him, then my body will not leave his body till either of us mee
Grade: Sahih

Hadith #3231 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Ka`b bin Ujrah met me and said, “Shall I not give you a present I got from the Prophet?” `Abdur- Rahman said, “Yes, give it to me.” I said, “We asked Allah’s Messenger (ﷺ) saying, ‘O Allah’s Messenger (ﷺ)! How should one (ask Allah to) send blessings on you, the members of the family, for Allah has taught us how to salute you (in the prayer)?’ He said, ‘Say: O Allah! Send Your Mercy on Muhammad and on the family of Muhammad, as You sent Your Mercy on Abraham and on the fa
Grade: Sahih

Hadith #3431 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
The companions of Suffa were poor people. The Prophet (ﷺ) once said, “Whoever has food enough for two persons, should take a third one (from among them), and whoever has food enough for four persons, should take a fifth or a sixth (or said something similar).” Abu Bakr brought three persons while the Prophet (ﷺ) took ten. And Abu Bakr with his three family member (who were I, my father and my mother) (the sub-narrator is in doubt whether `Abdur-Rahman said, “My wife and my servant who
Grade: Sahih

Hadith #3599 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
We asked Hudhaifa to tell us of a person resembling (to some extent) the Prophet (ﷺ) in good appearance and straight forward behavior so that we may learn from him (good manners and acceptable conduct). Hudhaifa replied, “I do not know anybody resembling the Prophet (to some extent) in appearance and conduct more than Ibn Um `Abd.
Grade: Sahih

Hadith #3674 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Al-Qasim used to walk in front of the funeral procession. He used not to get up for the funeral procession (in case it passed by him). And he narrated from `Aisha that she said, “The people of the pre-lslamic period of ignorance used to stand up for the funeral procession. When they saw it they used to say twice: ‘You were noble in your family. What are you now?”
Grade: Sahih

Hadith #3696 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
“I asked Masruq, ‘Who informed the Prophet (ﷺ) about the Jinns at the night when they heard the Qur’an?’ He said, ‘Your father `Abdullah informed me that a tree informed the Prophet (ﷺ) about them.’ “
Grade: Sahih

Hadith #3770 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I heard `Umar bin `Abdul-Aziz asking As-Sa’ib, the nephew of An-Nimr. “What have you heard about residing in Mecca?” The other said, “I heard Al-Ala bin Al-Hadrami saying, Allah’s Messenger (ﷺ) said: An Emigrant is allowed to stay in Mecca for three days after departing from Mina (i.e. after performing all the ceremonies of Hajj)”
Grade: Sahih

Hadith #3801 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
(the grandfather of Salih bin Ibrahim) the story of Badr, namely, the narration regarding the sons of ‘Afra’.
Grade: Sahih

Hadith #3808 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
“I had an agreement with Umaiya bin Khalaf (that he would look after my relatives and property in Mecca, and I would look after his relatives and property in Medina).” `Abdur-Rahman then mentioned the killing of Umaiya and his son on the day of Badr, and Bilal said, “Woe to me if Umaiya remains safe (i.e. alive) . “
Grade: Sahih

Hadith #3823 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
While I was fighting in the front file on the day (of the battle) of Badr, suddenly I looked behind and saw on my right and left two young boys and did not feel safe by standing between them. Then one of them asked me secretly so that his companion may not hear, “O Uncle! Show me Abu Jahl.” I said, “O nephew! What will you do to him?” He said, “I have promised Allah that if I see him (i.e. Abu Jahl), I will either kill him or be killed before I kill him.” Then the other said the same
Grade: Sahih

Hadith #5040 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
I heard Ibn `Abbas answering a man who asked him, “Did you attend the prayer of `Id al Adha or `Idal- Fitr with Allah’s Messenger (ﷺ)?” Ibn `Abbas replied, “Yes, and had it not been for my close relationship with him, I could not have offered it.” (That was because of his young age). Ibn `Abbas further said, Allah’s Messenger (ﷺ) went out and offered the Id prayer and then delivered the sermon.” Ibn `Abbas did not mention anything about the Adhan (the call for prayer) or the Iq
Grade: Sahih

Hadith #5168 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
We were one hundred and thirty men sitting with the Prophet. The Prophet (ﷺ) said, “Have anyone of you any food with him?” It happened that one man had one Sa of wheat flour (or so) which was turned into dough then. After a while a tall lanky pagan came, driving some sheep. The Prophet (ﷺ) asked, ‘Will you sell us (a sheep), or give (it to) us as a gift?” The pagan said, “No, but I will sell it ” So the Prophet bought from him a sheep which was slaughtered, and then the Prophet (
Grade: Sahih

Hadith #5212 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
We were sitting in the company of Hudhaifa who asked for water and a Magian brought him water. But when he placed the cup in his hand, he threw it at him and said, “Had I not forbidden him to do so more than once or twice?” He wanted to say, “I would not have done so,” adding, “but I heard the Prophet saying, “Do not wear silk or Dibaja, and do not drink in silver or golden vessels, and do not eat in plates of such metals, for such things are for the unbelievers in this worldly life
Grade: Sahih

Hadith #5908 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Abu Bakr invited a group of people and told me, “Look after your guests.” Abu Bakr added, I am going to visit the Prophet (ﷺ) and you should finish serving them before I return.” `Abdur-Rahman said, So I went at once and served them with what was available at that time in the house and requested them to eat.” They said, “Where is the owner of the house (i.e., Abu Bakr)?” `Abdur-Rahman said, “Take your meal.” They said, “We will not eat till the owner of the house comes.” `A
Grade: Sahih

Hadith #5909 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Abu Bakr came with a guest or some guests, but he stayed late at night with the Prophet (ﷺ) and when he came, my mother said (to him), “Have you been detained from your guest or guests tonight?” He said, “Haven’t you served the supper to them?” She replied, “We presented the meal to him (or to them), but he (or they) refused to eat.” Abu Bakr became angry, rebuked me and invoked Allah to cause (my) ears to be cut and swore not to eat of it!” I hid myself, and he called me, “O
Grade: Sahih

Hadith #6120 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Ka`b bin ‘Ujra met me and said, “Shall I give you a present? Once the Prophet (ﷺ) came to us and we said, ‘O Allah’s Messenger (ﷺ) ! We know how to greet you; but how to send ‘Salat’ upon you? He said, ‘Say: Allahumma Salli ala Muhammadin wa ‘ala `Ali Muhammadin, kama sal-laita ‘ala all Ibrahima innaka Hamidun Majid. Allahumma barik ‘ala Muhammadin wa ‘ala all Muhammadin, kama barakta ‘ala all Ibrahima, innaka Hamidun Majid.”
Grade: Sahih

Hadith #6381 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
The Prophet (ﷺ) said, “O `Abdur-Rahman bin Samura! Do not seek to be a ruler, because if you are given authority for it, then you will be held responsible for it, but if you are given it without asking for it, then you will be helped in it (by Allah): and whenever you take an oath to do something and later you find that something else is better than the first, then do the better one and make expiation for your oath.”
Grade: Sahih

Hadith #6478 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “(O `Abdur-Rahman!) Do not seek to be a ruler, for, if you are given the authority of ruling without your asking for it, then Allah will help you; but if you are given it by your asking, then you will be held responsible for it (i.e. Allah will not help you ) . And if you take an oath to do something and later on find another thing, better than that, then do what is better and make expiation for (the dissolution of) your oath.”
Grade: Sahih

Hadith #6596 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
On the authority of others, that the Prophet (ﷺ) said, “No Punishment exceeds the flogging of the ten stripes, except if one is guilty of a crime necessitating a legal punishment prescribed by Allah.”
Grade: Sahih

Hadith #6877 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
The Prophet (ﷺ) said, “O `Abdur-Rahman! Do not seek to be a ruler, for if you are given authority on your demand then you will be held responsible for it, but if you are given it without asking (for it), then you will be helped (by Allah) in it. If you ever take an oath to do something and later on you find that something else is better, then you should expiate your oath and do what is better.”
Grade: Sahih

Hadith #6878 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “O `Abdur-Rahman bin Samura! Do not seek to be a ruler, for if you are given authority on your demand, you will be held responsible for it, but if you are given it without asking for it, then you will be helped (by Allah) in it. If you ever take an oath to do something and later on you find that something else is better, then do what is better and make expiation for your oath.”
Grade: Sahih

Hadith #7047 - Sahih al-Bukhari - 'Abdur-Rahman bin Abi Bakra's father (Sahih al-Bukhari)
Ibn `Abbas was asked, “Did you offer the Id prayer with the Prophet?” He said, “Yes, had it not been for my close relation to the Prophet, I would not have performed it (with him) because of my being too young The Prophet (ﷺ) came to the mark which is near the home of Kathir bin As-Salt and offered the Id prayer and then delivered the sermon. I do not remember if any Adhan or Iqama were pronounced for the prayer. Then the Prophet (ﷺ) ordered (the women) to give alms, and they started s
Grade: Sahih

Hadith #165 - Sahih Muslim - 'Abdur-Rahman bin Abi Bakra's father (Sahih Muslim)
We were in the company of the Messenger of Allah (ﷺ) that he observed: Should I not inform you about the most grievous of the grave sins? (The Holy Prophet) repeated it three times, and then said: Associating anyone with Allah, disobedience to parents, false testimony or false utterance. The Prophet was reclining, then he sat up, and he repeated it so many times that we wished that he should become silent.
Grade: Sahih